From Grammatical Reflection to Textual Comprehension: On the Reading of a Micro-Story - Sánchez Jiménez, Santiago Urbano (Huarte de San Juan. Filología y Didáctica de la Lengua, 2025)
This article stems from the need to integrate grammar and discourse in the development of metalinguistic competence, considering that contextualised linguistic reflection, undertaken with rigour, favours the performance of communicative competence. Methodologically, it is proposed that access to the analysis of grammar in context be grounded in the gramatical and discursive knowledge closest to the student: the meaning within grammatical structures and the contextual information within texts and discourse. Using a micro-story as an example of a literary subgenre, seven linguistic reflection activities are suggested, allowing for the recognition of contextual and discursive patterns through grammar and, in turn, verifying how contextual factors and discursive patterns are reflected in grammar. Thus, the contextualised metalinguistic exercise (applied in a micro-story, for example) is a strategy that generates deeper textual comprehension inferences.